Measuring the force of punches and kicks among combat sport athletes using a modified punching bag with an embedded accelerometer - Busko, K.; Staniak, Z.; Szark Eckardt, M.; Nikolaidis, P. T.; Mazur-Rózycka, J.; Lach, P.; Michalski, R.; Gajewski, J.; Górski, M. (Acta of Bioengineering and Biomechanics, 2016)
The main aim of the study was to design a new system to measure punching and kicking forces as well as reaction times in combat sport athletes. In addition, the study examined whether there were any intergender differences in the force of punches thrown by boxers and kicking forces delivered by taekwondo athletes. Boxers (male, n = 13; female, n = 7) were examined for the force of single straight punches and taekwondo athletes (male, n = 14; female, n = 14) for force of single Apdolio and Dwit Chagi kicks. The punching bag was equipped with acceleration transducers and gyroscopes embedded in a cylinder covered with a layer to absorb shock as well as a set of colour signal diodes. Value of the punching bag`s acceleration was used for calculating: strike force; the punching location on the bag; and time of a strike. The relative error of force calculation was 3%; the relative error in acceleration measurement was less than 1%. The force of a straight rear-hand punch was greater than the force of a lead-hand punch among male and female boxers. The force of Apdolio kick delivered with a rear leg was greater compared to a lead leg among female and male taekwondo athletes. Significant gender differences were noticed in the force in both types of kicks. In boxers, intergender differences were reported only for the force of a punch thrown with the rear hand. Based on these findings, it was concluded that the modified punching bag is a good diagnostic tool for combat sports.